1995
DOI: 10.1530/eje.0.1320163
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effect of gonadotropin-releasing hormone (GnRH) on in vitro prolactin secretion and presence of GnRH specific receptors in a subset of human prolactinomas

Abstract: The purpose of this study was to determine whether gonadotropin-releasing hormone (GnRH) may exert a direct action on human prolactinomas. On a series of 17 adenomas, we studied the effect of GnRH on the in vitro prolactin (PRL) secretion of dispersed and perifused cells of 10 cases and the [125I]GnRH agonist binding on frozen sections of three out of the adenomas studied in perifusion and on the membrane preparations of seven other cases. Two 20-min pulses of GnRH (10(-7) mol/l) stimulated the in vitro PRL se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Indeed, ␣GSU may have an autocrine role in these PRL cells because it stimulates the development (25,37) and secretory activity of lactotrophs (38). Coexpression of PRL and ␣GSU, but not ␤GSUs, has been found in certain prolactinomas that also express the GnRH receptor in the same cells (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ␣GSU may have an autocrine role in these PRL cells because it stimulates the development (25,37) and secretory activity of lactotrophs (38). Coexpression of PRL and ␣GSU, but not ␤GSUs, has been found in certain prolactinomas that also express the GnRH receptor in the same cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that treatment of fetal mouse with diethylstilbestrol advanced the first appearance of lactotrophs as early as E14, which is earlier than the first detection of GH (57). The coexpression of PRL and ␣GSU mRNA and its up-regulation by GnRH is interesting in view of the report that part of human prolactinomas also coexpress these two genes in the same cells and that only these tumors were responsive to GnRH in terms of PRL secretion (39).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it has been shown that paradoxical responses to various stimuli occur in human pituitary tumors in vivo and in vitro [10]. A direct effect of GnRH on human prolactinoma cells and the presence of GnRH receptors on the cell surfaces have recently been reported [11]. GnRHresponding cells which contain GH antigens have been reported to be present in normal rat pituitary cells [ Rabbit antiserum to rat PRL was obtained from UCB-Bioproducts, (Brussels, Belgium), and guinea pig antisera to rat LHJ3 and FSHJ3 were obtained from the National Pituitary Agency (Baltimore, MD).…”
mentioning
confidence: 99%